Organizational Culture and Job Satisfaction: A Review - BELIAS, DIMITRIOS; KOUSTELIOS, ATHANASIOS (International Review of Management and Marketing, 2014)
The purpose of the present study is to provide a critical review of the relation between organizational culture and the levels of job satisfaction experienced by employees. Organizational culture refers to a series of attitudes and behaviors adopted by employees of a certain organization, which affect its function and total well-being. Job satisfaction refers to the employees’ perceptions of their working environment, relations among colleagues, earnings and promotion opportunities. The review shows that contemporary job-related phenomena like job satisfaction are related to their perceptions of their working environment, relations with colleagues, institution aims and strategies and success criteria. In addition, the employees’ preference of organizational culture is likely to be affected by demographic characteristics, especially gender. It can be supported, therefore, that measuring and analyzing an institution’s organizational culture in combination with its employees’ demographic and individual characteristics may lead to valuable conclusions, so that job satisfaction is promoted. Keywords: Organizational Culture; Job Satisfaction JEL Classifications: J24; M11; M12; M14; O15